The Timing of Pregnancy: Women’s Interpretations of Planned and Unplanned Pregnancy - Elena Neiterman; Yvonne LeBlanc (Qualitative Sociology Review, 2018)
In this paper, we apply the concept of timing to explore the meaning that women attach towards planned and unplanned pregnancy. We conducted qualitative semi-structured interviews with 42 Canadian women who were pregnant or recently gave birth to examine how they experience the transition to motherhood. We contend that the timing of pregnancy is a socially constructed norm that impacts women through a complex range of life events and circumstances. Participants’ accounts suggest a gamut of compliance, ambivalence, and defiance towards the “timing of pregnancy” standards. Situating women’s decisions on childbearing within the continuum of their life trajectories and societal expectations surrounding pregnancy allows for better understanding of the interplay between women’s personal choices and the social norms informing these decisions.